2012
DOI: 10.1152/jn.00122.2011
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of rat motoneuron rhythmic firing properties with varying levels of afferent and descending inputs

Abstract: MacDonell CW, Button DC, Beaumont E, Cormery B, Gardiner PF. Plasticity of rat motoneuron rhythmic firing properties with varying levels of afferent and descending inputs. J Neurophysiol 107: 265-272, 2012. First published September 28, 2011 doi:10.1152/jn.00122.2011.-Hindlimb motoneuron excitability was compared among exercise-trained (E), sedentary (S), and spinal cord transected (T) Sprague-Dawley rats by examining the slope of the frequency-current (F/I) relationship with standard intracellular recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…In animals, endurance training decreased the current required to discharge a motoneurone to fire but not the amount of current required to elicit an action potential 50% of the time (i.e. rheobase current) [47]. In humans, Van Cutsem et al [36] showed a shift in tibialis anterior motor unit recruitment thresholds (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, endurance training decreased the current required to discharge a motoneurone to fire but not the amount of current required to elicit an action potential 50% of the time (i.e. rheobase current) [47]. In humans, Van Cutsem et al [36] showed a shift in tibialis anterior motor unit recruitment thresholds (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in motoneurone properties between the non‐locomotor and locomotor states might be different in adult rats with different daily activity patterns (Barnett, ) compared to cats, given the increased excitability (Beaumont & Gardiner, , ) and decreased rate of adaptation (MacDonell et al . ) noted in ‘anaesthetized’ motoneurones in rats after endurance training.…”
Section: Introductionmentioning
confidence: 99%
“…) and have been shown to respond to training (Beaumont & Gardiner, , ; MacDonell et al . ) and disuse (Cormery et al . , ; Button et al .…”
Section: Introductionmentioning
confidence: 99%
“…More comprehensive reviews Gardiner 2006) of the changes observed in fast and slow MNs with different training loads suggests that these adaptations do not represent a simple shift in MN type but instead reflect more targeted changes in ionic conductances in different cell types that may function to enhance fatigue resistance during rhythmic firing. In keeping with this idea, exercise-trained animals (treadmill and voluntary wheel) exhibit a 40% lower rate of spike frequency adaptation and a lower frequency-current slope compared with controls (MacDonell et al 2012). These adaptations in rhythmic firing behaviour may optimize force production and allow MNs to maintain muscle output more efficiently during prolonged activity.…”
Section: Mns Adapt To Increased Physical Activitymentioning
confidence: 94%
“…However, intracellular recordings from cat and rat MNs reveal a paradoxical effect of spinal cord transection on MN excitability. Changes in both passive and active electrophysiological MN properties indicate a reduction in MN excitability in cats (Cope et al 1986;Czéh et al 1978;Hochman and McCrea 1994) and rats (Beaumont et al 2004(Beaumont et al , 2008Button et al 2008;MacDonell et al 2012). On the other hand, there is an increase in spastic contractions that may reflect the activation of PIC (Bennett et al 2001a(Bennett et al , 2001bCôté et al 2017), which would enhance MN excitability or polysynaptic reflexes.…”
Section: Spinal Cord Injurymentioning
confidence: 99%